Penafsiran Muhammad ‘Abduh Terhadap Alquran Surat Al-Nisâ’ Ayat 3 dan 129 tentang Poligami - Abdurrahman, U. (Universitas Islam Negeri Raden Intan Lampung, 2017)
Muhammad ‘Abduh is a pioneer and the founder of the Tafsîr al-Adab al-Ijtimâ’i school, a style of interpretation of the Koran that emphasizes to the beauty of language (literature) as well as to social criticism toward the improvement of society. According to Abduh, the verses 3 and 29 of Surah al-Nisa [4] does allow polygamy but with strict requirements and restrictions i.e being able to deal justly with wives. In addition, polygamy can only be done by a husband in a certain situation, such as in the inability of a wife to conceive or give birth. Beyond that, according to his view, polygamy should not be done or unlawful. In his interpretation, Abduh uses solution method (tahliliy) with a rational approach (bi al-ra’y) orientating to social demands (al-ijtimâ’i).